Anti-inflammatory effects of apocynin: a narrative review of the evidence. Issue 1 (1st January 2021) - Boshtam, Maryam; Kouhpayeh, Shirin; Amini, Farahnaz; Azizi, Yadollah; Najaflu, Malihe; Shariati, Laleh; Khanahmad, Hossein
Abstract : Inflammation is a vital process in response to injury and infection. However, hyper-inflammation have been linked to the pathophysiology of diseases such as atherosclerosis, cancers, neuroinflammatory, respiratory, renal diseases and Coronavirus disease 2019. Apocynin is known as a nontoxic herbal compound with anti-inflammatory potential. This review aimed to assess the effects of apocynin in the attenuation of inflammation and identify its mechanism of action based on a narrative review of available evidence. The reviewed literature has shown that apocynin exerts the immunomodulatory effect through reactive oxygen species-dependent and –independent approaches in phagocytic and non-phagocytic cells, respectively. In the reactive oxygen species-dependent pathway, apocynin monomers are converted to dimers, consequently inhibiting NADPH oxidase activation to reduce reactive oxygen species levels. While, in the reactive oxygen species-independent approach, apocynin directly reduces inflammatory cytokines and chemokines and increases nitric oxide without affecting reactive oxygen species levels. In conclusion, apocynin shows various minor macromolecular functions such as reducing chemokine synthesis, inhibiting cell migration and division, suppressing platelet/endothelial interaction and platelet aggregation, blood–brain barrier permeability, and decreasing reduction infarct volume. It is also hypothesized that apocynin might be considered a complementary remedy for Coronavirus disease 2019 due to its role in modulating inflammatory responses.